Konsep Akhir Zaman dalam Perspektif Agama, Dan Sains Serta Bagaimana Iman Kristen Menanggapinya Berdasarkan Kitab Wahyu - Dominikus Selfius Bain; Abad Jaya Zega (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This study explains the concept of the end times from the perspective of religion, science, and how the Christian faith responds to it by focusing on the contents of the Book of Revelation in the Bible. The concept of the end times is a relevant topic in Christian theology and has been the focus of debate throughout church history. From a religious perspective, the concept of the end times reflects views regarding the end of the world, resurrection, final judgment, and eternal life. Meanwhile, in the context of science, rational and scientific approaches often try to explain natural phenomena related to the end times, such as climate change, natural disasters and technological developments.This article also explores how the Christian faith describes the concept of the end times based on the Book of Revelation. The Book of Revelation is the passage in the New Testament known for the prophet John's vision of the end times, featuring rich symbolism. Priesthood, judgment, and restoration are all found in this text, and followers of Christ often look to it as a source of guidance regarding what will happen in the future. In discussing the Christian faith's response to the concept of the end times, this article details the various views and theologies that exist in the Christian tradition, such as premillennial, amillennial, and postmillennial eschatology. In addition, it also highlights some contemporary approaches that integrate theological understanding with scientific thinking about the future of the planet. This research provides a holistic view of how the concept of the end times is understood from the perspective of religion, science and Christian faith with a focus on the Book of Revelation in the Bible, as well as how these various understandings coexist in modern Christian theology. As a result, this article can help promote a deeper understanding of the meaning and implications of the concept of the end times in the context of religion, science, and the Christian faith.